2006
DOI: 10.1128/aem.72.5.3441-3447.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Fluoroquinolone-Resistant Campylobacter spp. within an Integrated Commercial Poultry Production System

Abstract: . The sequences exhibited high levels of similarity to Campylobacter jejuni and Campylobacter coli sequences, suggesting that chickens can carry Campylobacter at a very young age. Campylobacter sp. was detected by PCR in all samples collected from the ilea of chicks that were 3 to 49 days old; however, it was detected only in the cecal contents of chickens that were at least 21 days old. In order to determine whether the presence of Campylobacter DNA in young chicks was due to ingestion of the bacteria in food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 41 publications
(46 reference statements)
1
22
0
Order By: Relevance
“…Maruyama and Katsube in 1990 (55) demonstrated that Campylobacter could be transmitted to the offspring via the fertile egg after orally inoculating Japanese quail breeder hens. These findings were supported further by Idris et al (44).…”
Section: Campylobacter Association With the Fertile Eggsupporting
confidence: 75%
“…Maruyama and Katsube in 1990 (55) demonstrated that Campylobacter could be transmitted to the offspring via the fertile egg after orally inoculating Japanese quail breeder hens. These findings were supported further by Idris et al (44).…”
Section: Campylobacter Association With the Fertile Eggsupporting
confidence: 75%
“…egg surface contamination) however it seems that this research is still hampered by the sensitivity of isolation and genotyping techniques, which will be discussed later. Meta-analysis of two studies associated the hatchery source to Campylobacter colonization at the broiler level (OR = 4.8) [40], [41] and Idris et al demonstrated identical resistance patterns in the breeders and broilers [34]. Previous reviews that looked at vertical transmission concluded this was a low risk exposure route for Campylobacter in broilers [12], [13], however based on the evidence identified in this SR there is evidence that vertical transfer occurs and due to well documented isolation issues, we cannot conclude on the relative importance of this source compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…(Wallace et al 1998). However, recently, 16S rDNAs with ∼99% homology to C. jejuni and C. coli were detected in the ilea, yolk sac, and ceca of day-old chicks, which were culture-negative, suggesting either primary vertical transmission or transmission through the porous egg shell during incubation at the hatchery (Callicott et al 2006;Idris et al 2006;Pearson et al 1996).…”
Section: Amikmentioning
confidence: 94%